Uji Aktifi tas Antiinfl amasi Estrak Daun Cocor Bebek (Kalanchoe pinnata L) Terhadap Kaki Tikus (Rattus novergicus) - Andi Maulia; Ismail Ismail; Andi Tendriani Safitri; Ahmad Fadly Perdana (Fakultas Farmasi Universitas Pancasila, 2020)
Cocor bebek leaves contain fl avanoids which have anti-infl ammatory power by inhibitingprostaglandin synthesis by blocking the work of cyclooxygenase and inhibiting leukotriene by blockinglipookigenase. Infl ammation is a local protective response caused by damage to tissue caused by physicaltrauma, damaging chemicals, or microbiological substances. This study aims to determine the eff ect ofcocor bebek leaf extract as an anti-infl ammatory in leg edema of white mice (Rattus novergicus) with2% carrageenan induction. In this test using the in vivo activity test method for white rats (Rattusnovergicus) which has been induced by carrageenan. The volume of the rat’s feet is measured usinga pletismometer. Rats were divided into fi ve groups, the fi rst group as negative control were givendiclofenac sodium gel, groups two, three, four were given ethanol extract of leaves of cocor bebek 200,400 and 600 mg respectively, group fi ve as negative controls then calculated volume of feet. The resultsobtained, extract of 400 mg better anti-infl ammatory eff ects.